Trapping metallic particles using focused Bloch surface waves - Xiang, Yifeng (Nanoscale, 2020)
Metallic particles are promising for applications in various areas, including optical sensing, imaging and electric field enhancement-induced optical and thermal effects. The ability to trap or transport these particles stably will be important in these applications. However, while traditional optical tweezers can trap metallic Rayleigh particles easily, it is difficult to trap metallic mesoscopic/Mie particles because of the strong scattering forces that come from the far-field trapping laser beam. Here we demonstrate that metallic particles can be trapped stably using focused Bloch surface waves that propagate in the near-field region of a dielectric multilayer structure with a photonic band gap. Focused Bloch surface waves can be excited efficiently using an annular beam with azimuthal polarization and a high-numerical-aperture objective. Numerical simulations were performed to calculate the optical forces loaded on a gold particle by focused Bloch surface waves and the results were consistent with those of the experimental observations.